Spatial Pattern of Tourism Destination Areas on Bintan Island, Riau - Nurul Nadjmi (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2021)
One of the islands in the Riau Islands is Bintan, which is an island that has the capital of the Riau Islands Province, namely Tanjung Pinang. Bintan Island has a strategic location and abundant tourism objects, and one of the uniqueness of the tourism destination area on Bintan Island is the existence of a private or closed tourism destination area that allows tourists to enjoy their vacation without any outside interference or local residents' activities. The purpose of this study is to find out and analyze in depth about the spatial patterns of tourism destination areas in Bintan Island, Riau Islands. The scope of research in this discussion is focused on the spatial pattern of tourism destination areas located on Bintan Island, especially on private tourism areas. The research method used in this research is descriptive qualitative research. This research is conditioned as qualitative research through a case study strategy. The system approach used is also a descriptive analytic approach. Make direct observations, collect data and then relate it to the study of the theories used. Based on the results of a survey I conducted on Bintan Island, Riau, the distribution of tourist destination areas on Bintan Island is almost evenly distributed in every district in Bintan Island, there is a pattern of distribution related to tourism activities that is influenced by the attraction held by each destination area on the island.